Respons Siswa Terhadap Aplikasi Media Pembelajaran Interaktif Aritmetika Sosial Escape From Home - Asiah Hanifatul Huda; Dori Lukman Hakim (Qalam : Jurnal Ilmu Kependidikan, 2022)
Android has evolved into one of the most frequently used operating systems as a result of the advancement of technology. Android offers several advantages as a learning medium, including its accessibility and simplicity of use. The purpose of this research was to assess student responses to Social Arithmetic Escape From Home, an Android-based interactive learning media. This is a descriptive study of students' reactions to learning media technologies. The data was collected using a questionnaire that included questions about three areas of media assessment: appearance, ease of use, and benefits. The findings revealed that students' responses to the areas of appearance and simplicity of use were very positive, with percentage scores of 95.8% and 89.2%, respectively. The benefits aspect has a score percentage of 73.6% in the positive response category. The Escape From Home Social Arithmetic application as an Android-based interactive learning medium received a very positive response and was practically implemented in learning, with an average percentage score of 86.2% in the very positive response category. Keywords : android, students response, interactive, social arithmetic